(untitled) (Analysis in Theory and Applications, 2025)
In this paper, we consider the stationary Kirchhoff-type equation with mixed boundary conditions in a variable exponent Sobolev space. We show the existence of a weak solution. Moreover, we prove the existence of a non-trivial weak solution and infinitely many weak solutions under some hypotheses by variational methods.